Modelling and optimisation of intermediate pyrolysis synthesis of bio-oil production from palm kernel shell - Imhade P. Okokpujie; Anthony O. Onokwai; Ejiroghene Onokpite; Kunle Babaremu; Emmanuel S.A. Ajisegiri; Christian O. Osueke; Stephen A. Akinlabi; Esther T. Akinlabi (Cleaner Engineering and Technology, 2023)
A Palm Kernel Shell (PKS) is an enclosed shell obtained as residue from processing palm kernel. Its regarded as lignocellulosic biomass that serves as an abundant renewable energy source. The thermal and physicochemical behaviour was investigated, and results showed a low Fixed Carbon (FC) (22.60 wt%), high Volatile Matter (VM) (74.60 wt%), and high Higher Heating Value (HHV) of 19.78 MJ/kg. The elemental results showed the presence of C (48.70 wt%), H (5.58 wt%), N (0.23 wt%), O (45.02 wt%), and S (0.04 wt%). The fixed-bed pyrolysis reactor was utilised for the decomposition of the PKS to produce an optimum bio-oil of 47.10 wt% at temperature (520 °C), reaction time (15 min), nitrogen (175 cm3/min), particle size (0.70 mm), and heating rate (22.5 °C/min). The efficient Response Surface Methodology (RSM) via Central Composite Design (CCD) was employed to model and optimise the operating parameters. P<0.05, a high F-value for bio-oil makes the established model predicted, suitable, responsive, and reliable. The actual and predicted value for the quantity of bio-oil produced showed clearly that the data is reasonably in consonance with the predicted value. Screening with FT-IR revealed that the peak of 3339.7, 1416 cm−1 attributed to O–H stretching vibrations depicted the presence of alcohol and carboxylic acids, respectively, the resent, while the peak at 1636.3, 1274.7 was due to C–H bend and C–O stretch indicating the presence of aromatic compounds and aromatic ester respectively. The most significant element in the bio-oil obtained via Gas Chromatography–Mass Spectrometry (GC–MS) analysis is phenol, 9, 17 – octadecadienoyl, oleic acids, 2-cyclo pentane-1-one, and pent ethylene glycol are the by-products in the sample. Hence, the bio-oil produced is suitable for high-speed diesel engines, vehicle locomotion, powering heavy machines, marine equipment, manufacturing industries, and mining types of machinery. This is a significant contribution in the field of bio-oil production and application.